22q11.2q13 duplication including SOX10 causes sex-reversal and peripheral demyelinating neuropathy, central dysmyelinating leukodystrophy, Waardenburg syndrome, and Hirschsprung disease. - Falah, Nadia; Posey, Jennifer E; Thorson, Willa; Benke, Paul; Tekin, Mustafa; Tarshish, Brocha; Lupski, James R; Harel, Tamar (Am J Med Genet A, 2017)
Diagnosis of genetic syndromes may be difficult when specific components of a disorder manifest at a later age. We present a follow up of a previous report [Seeherunvong et al., (2004); AJMGA 127: 149-151], of an individual with 22q duplication and sex-reversal syndrome. The subject's phenotype evolved to include peripheral and central demyelination, Waardenburg syndrome type IV, and Hirschsprung disease (PCWH; MIM 609136). DNA microarray analysis defined the duplication at 22q11.2q13, including SOX10. Sequencing of the coding region of SOX10 did not reveal any mutations. Our data suggest that SOX10 duplication can cause disorders of sex development and PCWH, supporting the hypothesis that SOX10 toxic gain of function rather than dominant negative activity underlies PCWH.
Keywords: 46, XX Testicular Disorders of Sex Development; African Americans; Chromosome Duplication; Chromosomes, Human, Pair 22; Demyelinating Diseases; Hirschsprung Disease; Humans; Kidney Failure, Chronic; Male; Pelizaeus-Merzbacher Disease; SOXE Transcription Factors; Waardenburg Syndrome

Efficient CNV breakpoint analysis reveals unexpected structural complexity and correlation of dosage-sensitive genes with clinical severity in genomic disorders. - Zhang, Ling; Wang, Jingmin; Zhang, Cheng; Li, Dongxiao; Carvalho, Claudia M B; Ji, Haoran; Xiao, Jianqiu; Wu, Ye; Zhou, Weichen; Wang, Hongyan; Jin, Li; Luo, Yang; et al. (Hum Mol Genet, 2017)
Genomic disorders are the clinical conditions manifested by submicroscopic genomic rearrangements including copy number variants (CNVs). The CNVs can be identified by array-based comparative genomic hybridization (aCGH), the most commonly used technology for molecular diagnostics of genomic disorders. However, clinical aCGH only informs CNVs in the probe-interrogated regions. Neither orientational information nor the resulting genomic rearrangement structure is provided, which is a key to uncovering mutational and pathogenic mechanisms underlying genomic disorders. Long-range polymerase chain reaction (PCR) is a traditional approach to obtain CNV breakpoint junction, but this method is inefficient when challenged by structural complexity such as often found at the PLP1 locus in association with Pelizaeus-Merzbacher disease (PMD). Here we introduced 'capture and single-molecule real-time sequencing' (cap-SMRT-seq) and newly developed 'asymmetry linker-mediated nested PCR walking' (ALN-walking) for CNV breakpoint sequencing in 49 subjects with PMD-associated CNVs. Remarkably, 29 (94%) of the 31 CNV breakpoint junctions unobtainable by conventional long-range PCR were resolved by cap-SMRT-seq and ALN-walking. Notably, unexpected CNV complexities, including inter-chromosomal rearrangements that cannot be resolved by aCGH, were revealed by efficient breakpoint sequencing. These sequence-based structures of PMD-associated CNVs further support the role of DNA replicative mechanisms in CNV mutagenesis, and facilitate genotype-phenotype correlation studies. Intriguingly, the lengths of gained segments by CNVs are strongly correlated with clinical severity in PMD, potentially reflecting the functional contribution of other dosage-sensitive genes besides PLP1. Our study provides new efficient experimental approaches (especially ALN-walking) for CNV breakpoint sequencing and highlights their importance in uncovering CNV mutagenesis and pathogenesis in genomic disorders.
Keywords: Base Sequence; Comparative Genomic Hybridization; DNA Copy Number Variations; DNA Replication; Female; Gene Dosage; Gene Duplication; Gene Rearrangement; Genetic Association Studies; Genome, Human; Genomics; Humans; Male; Mutation; Pelizaeus-Merzbacher Disease; Sequence Analysis, DNA

Complex genomic rearrangements at the PLP1 locus include triplication and quadruplication. - Beck, Christine R; Carvalho, Claudia M B; Banser, Linda; Gambin, Tomasz; Stubbolo, Danielle; Yuan, Bo; Sperle, Karen; McCahan, Suzanne M; Henneke, Marco; Seeman, Pavel; Garbern, James Y; Hobson, Grace M; et al. (PLoS Genet, 2015)
Inverted repeats (IRs) can facilitate structural variation as crucibles of genomic rearrangement. Complex duplication-inverted triplication-duplication (DUP-TRP/INV-DUP) rearrangements that contain breakpoint junctions within IRs have been recently associated with both MECP2 duplication syndrome (MIM#300260) and Pelizaeus-Merzbacher disease (PMD, MIM#312080). We investigated 17 unrelated PMD subjects with copy number gains at the PLP1 locus including triplication and quadruplication of specific genomic intervals-16/17 were found to have a DUP-TRP/INV-DUP rearrangement product. An IR distal to PLP1 facilitates DUP-TRP/INV-DUP formation as well as an inversion structural variation found frequently amongst normal individuals. We show that a homology-or homeology-driven replicative mechanism of DNA repair can apparently mediate template switches within stretches of microhomology. Moreover, we provide evidence that quadruplication and potentially higher order amplification of a genomic interval can occur in a manner consistent with rolling circle amplification as predicted by the microhomology-mediated break induced replication (MMBIR) model.
Keywords: Chromosome Breakpoints; Chromosome Inversion; Gene Dosage; Gene Duplication; Humans; Myelin Proteolipid Protein; Pelizaeus-Merzbacher Disease